2022
DOI: 10.3389/fneur.2022.929569
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of sleep structure in Parkinson's disease patients with hallucinations based on polysomnography

Abstract: Hallucination is a common non-motor symptom in patients with Parkinson's disease (PD). Additionally, sleep disorders are associated with an increased risk of hallucinations in PD patients. This study aimed to examine the association between hallucination and objective sleep parameters in PD patients. We retrospectively recruited 278 PD patients who underwent polysomnography and clinical assessments and classified them into non-hallucination and hallucination groups. Hallucinations were observed in 77 older PD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…This rigorous screening ensured that only the most relevant articles were considered for further examination in our review. After assessing 261 full papers for eligibility, only 29 studies fulfilled the necessary criteria and underwent data extraction ( Figure 1 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Among the 232 full-text articles excluded, none met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This rigorous screening ensured that only the most relevant articles were considered for further examination in our review. After assessing 261 full papers for eligibility, only 29 studies fulfilled the necessary criteria and underwent data extraction ( Figure 1 ) [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Among the 232 full-text articles excluded, none met the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Considering the absence of a specific tool for assessing OHs in PD patients, most authors opted to interview patients using semi-structured questionnaires or non-specific questions related to the presence of phantosmia [ 16 , 18 , 19 , 25 , 27 , 28 , 29 , 32 , 33 , 35 , 42 , 43 ]. Other authors assessed phantosmia in PD patients using structured questionnaires or interviews, including the Neuropsychiatric Inventory (NPI), the Schedule for Assessment of Positive Symptoms (SAPS), the Enhanced Scale for Assessment of Positive Symptoms in Parkinson’s Disease (eSAPS-PD), the MDS-UPDRS hallucinations and psychosis item, the Psycho-Sensory hAllucinations Scale (PSAS), the Psychosis and Hallucinations Questionnaire (PsycH-Q), and the University of Miami Parkinson’s disease Hallucinations Questionnaire (UM-PDHQ) [ 17 , 20 , 21 , 22 , 23 , 24 , 26 , 30 , 31 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 44 ]. However, the available data in the literature did not identify the most appropriate tool to assess the presence of phantosmia in PD patients.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the increase in nocturnal arousal events may be of great value in predicting the progression of motor dysfunction in PD. Our recent study found that N3 sleep (slow-wave sleep, SWS) is one of the important risk factors in PD patients with hallucinations ( 49 ). The deconstruction of the sleep structure is a process affected by many complex factors.…”
Section: Discussionmentioning
confidence: 99%